2018
DOI: 10.3389/fpsyt.2018.00567
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions and Prevention of Suicide

Abstract: Over the past years, there has been a growing interest in the association between lifestyle psychosocial interventions, severe mental illness, and suicide risk. Patients with severe mental disorders have higher mortality rates, poor health states, and higher suicide risk compared to the general population. Lifestyle behaviors are amenable to change through the adoption of specific psychosocial interventions, and several approaches have been promoted. The current article provides a comprehensive review of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 135 publications
1
36
1
Order By: Relevance
“…Finally, the weather has a significant impact on social activities and interactions, especially in vulnerable populations. Interpersonal stress, low social connectedness, and poor social support have been recognized as major risk factors for suicide (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the weather has a significant impact on social activities and interactions, especially in vulnerable populations. Interpersonal stress, low social connectedness, and poor social support have been recognized as major risk factors for suicide (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, work-related or personal problems are also causing modern young people to move their homes without settling down. Such changes mean the lack of opportunities to share their lives, including meals, with family or other close social partners, affecting physical health, cognition, emotional state, and behavior [20][21][22]. Most Korean adults either skip breakfast or eat the meal away from home.…”
Section: Introductionmentioning
confidence: 99%
“…The review of lifestyle interventions related to suicide prevention [10] concluded that "lifestyle behaviours including cigarette smoking, alcohol use, and sedentary lifestyle are associated with suicide risk in all age groups" and for adults, "psychiatric symptoms, substance and alcohol abuse, weight, and occupational difficulties seem to have a significant role in suicide risk. However, most of the research cited in adults focuses on people with a history of chronic mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Jacka and Berk [9] proposed that diet, exercise and smoking are independent risk factors for depression. A review [10] of lifestyle interventions related to suicide prevention noted that alcohol use, smoking and sedentary lifestyles were risk factors for all ages. They also noted that other risk factors varied by age group, with psychiatric symptoms, substance and alcohol use, weight and occupational difficulties being pertinent in adults and organic disease and poor social support being risk factors in the elderly.…”
Section: Introductionmentioning
confidence: 99%